2011
DOI: 10.1111/j.1601-0825.2011.01861.x
|View full text |Cite
|
Sign up to set email alerts
|

A gene expression profile for non‐smoking and non‐drinking patients with head and neck cancer

Abstract: Differentially expressed genes in non-smoking and non-drinking patients possibly indicate the presence of a different cellular response to carcinogenic events in these patients. Further studies are warranted to validate this gene set and explore possible therapeutic implications to improve prognosis for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 22 publications
5
38
0
Order By: Relevance
“…In line with the increased interferon-γ activation previously observed in HNSCC from NSND [22], we observed that OSCC from NSND were strongly enriched for IFN-γ response.…”
Section: Discussionsupporting
confidence: 90%
“…In line with the increased interferon-γ activation previously observed in HNSCC from NSND [22], we observed that OSCC from NSND were strongly enriched for IFN-γ response.…”
Section: Discussionsupporting
confidence: 90%
“…A gene expression signature for this subtype was predictive of atypical HNSCC features in independent patient population data sets from two previous studies (Walter et al, 2013, Wichmann et al, 2015). Moreover, the CIMP-Atypical subtype displayed differential expression of genes previously reported as markers of non-smoking, non-drinking OSCCs (Farshadpour et al, 2012), that we found to be reproducibly associated with atypical HNSCC. This confirms that atypical HNSCCs display distinct gene expression patterns independent of anatomic subsite.…”
Section: Discussionsupporting
confidence: 56%
“…To further validate the CIMP-Atypical subtype, we examined a previously reported set of genes that were differentially expressed in non-smoking, non-alcohol related HNSCC relative to smoking and alcohol related HNSCC (Farshadpour et al, 2012) including 28 upregulated, and 21 downregulated genes. This study included only OSCC and oropharyngeal HNSCCs, sites primarily associated with HPV − HNSCC; therefore these gene signatures were considered putative atypical signatures: We confirmed this by validating these signatures as associated with atypical HNSCC within the TCGA, GSE65858, and GSE39366 studies (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations